Size and morphology-controlled synthesis of Ni3C nanoparticles in a TEG solution and their magnetic properties. Issue 85 (30th August 2016) - Zhang, Yajing; Zhu, Yuan; Cao, Yan; Li, Da; Zhang, Zhidong; Wang, Kangjun; Ding, Fu; Wang, Xiaolei; Meng, Dan; Fan, Lihui; Wu, Jing
Abstract : Nickel carbide nanoparticles (Ni3 C NPs) were synthesized by a polyol solution refluxing route at a temperature of 300 °C for 20 min using triphenylphosphine oxide (TPPO) as the surfactant. Abstract : Nickel carbide nanoparticles (Ni3 C NPs) were synthesized by a polyol solution refluxing route at a temperature of 300 °C for 20 min using triphenylphosphine oxide (TPPO) as the surfactant. Size and morphologies of the Ni3 C NPs were controlled by adjusting the concentration of Ni(NO3 )2 and TPPO. The products consisted of Ni and Ni3 C could be kinetically controlled by a reaction temperature of 250–290 °C and time less than 20 min and the proportion of the Ni component was lower with longer reaction times and higher temperatures due to carbon atom insertion via a carbonaceous film that formed on the surface of the growing particles. The formation process of the Ni3 C NPs was investigated by X-ray diffraction (XRD), scanning electron microscopy (SEM), high-resolution transmission electron microscopy (HRTEM), and X-ray photoelectron spectroscopy (XPS) characterization. The saturation magnetizations of products decreased with decreasing ratio of Ni : Ni3 C, which inferred that Ni3 C was non-magnetic and the magnetism arose from trace Ni in the products.